IMPLEMENTASI KEBIJAKAN BANTUAN SISWA MISKIN SEKOLAH DASAR DI KECAMATA TEMBALANG, KOTA SEMARANG - Didik Nugroho; Hesti Lestari; Slamet Santoso (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Research Policy Implementation Help Poor Students in Elementary School District Tembalang a qualitative descriptive study. This study uses the precision of a policy to explain the effectiveness of policy implementation Help Poor Students. The focus of this research that the Policy Implementation Assistance Poor Students in Elementary School District Tembalang using Grindle implementation model to analyze the factors in the implementation of policies that are used to determine the success of the policy implementation process. Informants in this study is from the Education Office of Semarang, UPTD District Tembalang, elementary schools in the District Tembalang, School Committee, Board of Education of Semarang, and Receiving Communities BSM. Research and analysis process begins from the state of education, describe the implementation process by using the appropriateness of the policy to assess the effectiveness and efficiency of policies Help Poor Students. Furthermore, analyzing the factors implementations using Grindle models to be able to see the success of the implementation of the policy Help Poor Students. With so can find out shortcomings in the implementation process so that it can be improved so that the implementation of a policy Help Poor Students can run effectively and efficiently